Epidemiological and clinical features of diabetic foot in Cotonou - KEREKOU HODE, ANNELIE; Djrolo, Isaie (My University, 2015)
This was a retrospective and descriptive study conducted from 1 July 2006 to 31 July 2011 and carried on 122 cases of diabetic foot collected a total of 706 diabetic patients hospitalized over a period of 5 years. Objective: To study the characteristics of diabetic feet in Cotonou. Results: The mean age of patients was 58.05 years ± 10.65 years, ranging from 35 years to 70 years. The sex ratio was 1.5. Duration of diabetes before the onset of diabetic foot was 11 years. The overall prevalence of diabetic foot was 21.53%. Of these, 95% had neuropathy, 70.40% had arterial disease and all had a foot infection. The amputation rate was 31.96% and the mortality rate was 17.21%. Conclusion: The occurrence of diabetic foot is earlier than in the West, and hence there is a need for early treatment of diabetes.
Keywords: diabetes; diabetic foot; Bénin; Africa